2008
DOI: 10.1097/id.0b013e3181776c52
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Dental Implant Failure Associated With Nasopalatine Duct Cyst

Abstract: This case report presents an analysis of the clinical, radiographic, and histological features of a peri-implant lesion around an implant placed immediately after extraction of a tooth with a periapical lesion. A 52-year-old man received an immediate implant (3.75 x 11.5 mm2) placed in the anterior region of the maxilla. Three years after implant placement, the patient presented with swelling in the anterior portion of the maxilla. Radiographic examination showed a well-circumscribed radiolucency around the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 16 publications
0
37
0
1
Order By: Relevance
“…Shortening of canal and enlargement of the IC diameter by tooth loss were also reported 3,6 . Insertion of implants into the IC may lead to contact of implants with nervous tissue and cause non‐osseointegration or lead to sensory alteration 9,10 . With increasing demand for rehabilitation of edentulous sites using implants, preoperative evaluation with three‐dimensional (3D) imaging gained attention, but studies examining IC anatomy are scarce.…”
mentioning
confidence: 99%
“…Shortening of canal and enlargement of the IC diameter by tooth loss were also reported 3,6 . Insertion of implants into the IC may lead to contact of implants with nervous tissue and cause non‐osseointegration or lead to sensory alteration 9,10 . With increasing demand for rehabilitation of edentulous sites using implants, preoperative evaluation with three‐dimensional (3D) imaging gained attention, but studies examining IC anatomy are scarce.…”
mentioning
confidence: 99%
“…Takeshita et al [4] reported the successful treatment of a peri-implant lesion that involved a third of the implant. If the implant is immobile (with good osseointegration) and the periapical lesion has not caused much damage to it, the implant can be kept in place by resecting the lesion with only the involved segment of the implant [4,12]. Accordingly, in our case, we decided to remove only the lesion because the implant itself showed no signs of mobility or peri-implant bone resorption and because only a small part of the implant was exposed to the lesion.…”
Section: Discussionmentioning
confidence: 97%
“…Casado et al [12] reported the removal of a placed implant because of a cystic lesion that negatively affected osseointegration; furthermore, the presence of the implant in the lesion could cause secondary infection of the bone, possibly leading to the development of osteomyelitis [13,14]. Takeshita et al [4] reported the successful treatment of a peri-implant lesion that involved a third of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…4 The choice of risking damage to the sinus wall using the osteotome technique with a bone graft in a site with a residual alveolar process suffi cient for inserting an implant of a slightly shorter length, with a prognosis often equal to a longer implant, can be criticised.…”
Section: Practicementioning
confidence: 99%